Guaranteed Cost Control for Uncertain Neutral Systems with a Minimal Order Observer - Erwin Susanto; Junartho Halomoan; Mitsuaki Ishitobi (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2015)
This paper presents a design scheme of a minimal order observer-based guaranteed cost controller for uncertain neutral systems, in which some state variables can not be measured. The uncertainties are assumed to be norm-bounded. The initial state is assumed unknown but their mean and covariance are assumed known. A sufficient condition for robust stability analysis and robust stabilization are derived via linear matrix inequalities (LMIs). To show the advantage of the proposed method, a numerical example is given.